Inequalities in Specialist Hand Surgeon Distribution across the United States. Issue 5 (May 2016) - Rios-Diaz, Arturo J.; Metcalfe, David; Singh, Mansher; Zogg, Cheryl K.; Olufajo, Olubode A.; Ramos, Margarita S.; Caterson, Edward J.; Talbot, Simon G.
Abstract : Background: Unequal access to hospital specialists for emergency care is an issue in the United States. The authors sought to describe the geographic distribution of specialist hand surgeons and associated factors in the United States. Methods: Geographic distributions of surgeons holding a Subspecialty Certificate in Surgery of the Hand and hand surgery fellowship positions were identified from the American Board of Medical Specialties Database and the literature (2013), respectively. State-level population and per capita income were ascertained using U.S. Census data. Variations in hand trauma admissions were determined using Healthcare Cost and Utilization Project national/state inpatient databases. Risk-adjusted generalized linear models were used to assess independent association between hand surgeon density and hand trauma admission density, fellowship position density, and per capita income. Results: Among 2019 specialist hand surgeons identified, 72.1 percent were orthopedic surgeons, 18.3 percent were plastic surgeons, and 9.6 percent were general surgeons. There were 157 hand surgery fellowship positions nationwide. There were 149, 295 annual hand trauma admissions. The national density of specialist hand surgeons and density of trauma admission were 0.6 and 47.6, respectively. The density of specialist hand surgeons varied significantly between states. State-level variations in density of surgeons were independent and significantly associated with median per capita income ( p < 0.001) and with density of fellowships ( p = 0.014). Conclusions: Specialist hand surgeons are distributed unevenly across the United States. State-level analyses suggest that states with lower per capita incomes may be particularly underserved, which may contribute to regional disparities in access to emergency hand trauma care. Abstract : Supplemental Digital Content is available in the text.This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.